إدارة تنظيم برنامج إذاعة "محبة“ للغة العربية براديو إلباس 97،6 إف إم بنجكولو - Agustian Rahmadi; Karunia Kholifah Dini Agustin; Zakiyah Arifa (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
Organizing is the second step in organization management after planning. An excellent organization produces a good form of organization, ranging from workplace systems, structures, resources to other aspects. This research discusses: organizing management in the Arabic program and division of duties in organizing the Arabic language program "Mahabbah" on Elbas 97.6 FM radio Bengkulu. This research uses the descriptive qualitative method. Data collection is conducted in interviews and observations directly to the head of labor, administrators, broadcasters. After the collected data is done through a) reduction of data, b) presentation of data, c) withdrawal of conclusions. This study showed that 1) organizing management in Elbas 97.6 FM radio program using coordination system can be seen from the duties of a radio announcer under the auspices of division, programmer, labor head, radio news manager, director, and commissioner. The Arabic program, in general, has a model of the structure of the line and staff. Therefore, the Arabic language program is presented after coordination with the interrelated staff. The broadcaster of the Arabic language program consists of two broadcasters who have different tasks. The division of functions is done so that the material presented can be delivered in Arabic and can be understood easily by the listener with the description using Indonesian 2) The division of tasks in the Arabic language program in organizing is clear and structured. Each broadcaster of the Arabic program has a planning task consisting of planning the presentation of materials and content that is inseparable from the nuances of Arabic, organizing the functions shared by each broadcaster. Broadcaster 1 has the core task of presenting Arabic language material with subtitles. In contrast, the 2nd broadcaster explains the presentation of broadcaster 1 so that listeners can understand the material and content offered, briefing, and supervision to regenerate the next broadcaster by conducting mentoring for two weeks. In addition to mentoring, broadcasters supervise the running of Arabic language programs so that the programs presented can achieve the desired goals.